Gambhari (Gmelina arborea Roxb. Ex Sm.) : A comprehensive analytical review of its therapeutic formulations from selected texts of Ayurveda. - Vijaya Lekshmi; Bhavna B Kapdiya; M Brajitha; G Sreebala; Bhupesh R Patel (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Gambhari (Gmelina arborea Roxb.) is a renowned medicinal plant used in Ayurveda. It is a fast-growing species that has proven antioxidant, immunomodulatory, anti-inflammatory, analgesic activities. Objective: The objective of this review was to conduct a comprehensive analysis of the therapeutic formulations of Gambhari mentioned in selected textbooks of Ayurveda focusing on the major srotas of their action, route of administration, dosage form used for the therapeutic delivery, part used, synonym used and whether the mode of administration was internal or external or both. Materials and Methods: This is a analytical review. The data compilation was made by a thorough analysis of 21 selected books of Ayurveda. Formulations containing any part of Gambhari whether utilized as a standalone ingredient or as constituents of Dasamula or Brhat Panchamoola were identified and documented in a specially designed data extraction sheet. NAMASTE (National AYUSH Morbidity and Standardized Terminologies Electronic) portal was referred for the English equivalents of Ayurvedic technical terms. Results: The analysis revealed that Gambhari was used as an ingredient in a total of 1125 formulations from 21 classical texts which were used for either internal or external administration or both. Among these 273 formulations were repeated. After removal of repetitions a total of 852 formulations acting on different diseases were obtained. The primary systemic affinities were visualized using Sunburst charts, illustrating the top five Srotas/ Srotas combinations targeted by these formulations. Conclusion: The current review highlights Gambhari (G.arborea) as a versatile therapeutic agent having a profound multi-target pharmacological profile. The review has demonstrated the primary affinity of the formulations containing Gambhari in Annavaha-Rasavaha and Pranavaha srotas highlighting its critical role in maintaining digestive metabolic and respiratory health.